Comparison of Landing Biomechanics Between Male and Female Dancers and Athletes, Part 2: Influence of Fatigue and Implications for Anterior Cruciate Ligament Injury. (May 2014) - Liederbach, Marijeanne; Kremenic, Ian J.; Orishimo, Karl F.; Pappas, Evangelos; Hagins, Marshall
Background: Fatigue is strongly linked to an increased risk of injuries, including anterior cruciate ligament (ACL) ruptures. Part 1 of this study identified differences in the biomechanics of landing from a jump between dancers and team athletes, particularly female athletes, which may explain the epidemiological differences in ACL injuries between dancers and team athletes and the lack of a sex disparity within dancers. However, it is not known if these biomechanical variables change differently between team athletes and dancers in the face of fatigue. Purpose/Hypothesis: The purpose of this study was to compare dancers' and team athletes' resistance to fatigue and its effect on the biomechanics of single-legged drop landings. The primary hypotheses were that dancers may be more resistant than team athletes to the onset of fatigue and/or may have different biomechanical responses than athletes in landing tasks once fatigue has been achieved. Study Design: Controlled laboratory study. Methods: Kinematics and kinetics were recorded as 40 elite modern and ballet dancers (20 men and 20 women) and 40 team sport athletes (20 men and 20 women; National Collegiate Athletic Association Division I-III) performed single-legged drop landings from a 30-cm platform before and after a fatigue protocol consisting of step-ups and vertical jumps. Unfatigued and fatigued joint kinematics and kinetics were compared between groups and sexes with multivariate analyses of variance, followed by pairwise t tests as appropriate. Results: Dancers took longer ( P = .023) than team athletes to reach a similar state of fatigue. Multiple kinetic (eg, increased peak knee valgus moment; P < .001) and kinematic (eg, increased lateral and forward trunk flexion; P < .001 and P = .002, respectively) parameters of landing changed with fatigue, such that both fatigued dancers and athletes landed with mechanics that were more at risk for ACL injuries as compared with before fatigue. Conclusion: Dancers took significantly longer to reach fatigue than team athletes. Female athletes consistently exhibited landing patterns associated with a risk for ACL injuries when compared with the other 3 groups. Fatigue changed landing mechanics similarly in both dancers and athletes, such that all groups landed with worse alignment after being fatigued. Clinical Relevance: Dancers are more resistant to lower extremity fatigue than athletes, and this may partially explain the lower incidence of ACL injuries in both male and female dancers compared to team athletes. The extensive training in landing technique and daily practice that dancers undergo from a young age may be responsible for the higher levels of endurance.